Pengaruh Leverage, Political Connection, dan Ukuran Perusahaan terhadap Kinerja Perusahaan - Fatma Febiana; Maulida Luthfiah Hanum; Putri Ayu Listiyaningrum; Sonia Angela Riawan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine whether there is influence between leverage, political connection, and company size on company performance. In this study, the population used are technology sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The type of data used is secondary data with financial reports as a reference. The sampling technique used is purposive sampling method and the total of research samples are 17 companies with 3 years period so that the total of observation data amounted to 51. The analytical method used in this study is panel data regression method with factor analysis using IBM SPSS Version 25. The results of this study indicate that leverage and political connections have no effect on firm performance (ROA). Meanwhile, firm size has an influence on firm performance (ROA).